2016
DOI: 10.1080/19768354.2016.1165288
|View full text |Cite
|
Sign up to set email alerts
|

miR-143 inhibits proliferation and induces apoptosis of mammary epithelial cells in dairy goat

Abstract: MicroRNAs are a class of post-transcriptional regulators of gene expression in multicellular organisms, which play important roles in cell fate, organ morphogenesis and carcinogenesis. In the present study, we demonstrated the critical roles of miR-143 on mammary epithelial cells of dairy goat. The test results of cell count, methylthiazolyldiphenyl-tetrazolium bromide, Hoechst33342/PI (propidium iodide) and flow cytometry showed miR-143-induced G0/G1 phase arrest, inhibited proliferation and promoted apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Ji et al (2015) showed that prolactin receptor is a target gene of miR-135a that may play a key role in regulating the development and lactation of caprine mammary gland [ 30 ]. MiR-143 is a crucial post-transcription regulator that is related to caprine mammary cell survival, and it may have an effect on the development, lactation or involution of mammary gland [ 31 ]. Dong et al (2013) suggested that miR-423-5p, miR-378 and miR-7 could have important regulatory functions during lactation with respect to milk ingredient transport and milk ingredient synthesis in the mammary gland [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ji et al (2015) showed that prolactin receptor is a target gene of miR-135a that may play a key role in regulating the development and lactation of caprine mammary gland [ 30 ]. MiR-143 is a crucial post-transcription regulator that is related to caprine mammary cell survival, and it may have an effect on the development, lactation or involution of mammary gland [ 31 ]. Dong et al (2013) suggested that miR-423-5p, miR-378 and miR-7 could have important regulatory functions during lactation with respect to milk ingredient transport and milk ingredient synthesis in the mammary gland [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…miR-143 appeared to be expressed at relatively high levels in adipose or mammary gland tissues ( Gu, Eleswarapu & Jiang, 2007 ). Our study showed that miR-143-induced mammary epithelial cell arrest in the G0/G1 phase delayed the progression of the cell cycle and inhibited cell proliferation ( Ji et al, 2016 ). Furthermore, miR-143 inhibits the proliferation and promotes the apoptosis of mammary gland epithelial cells by targeting and regulating the expression of Ndfip1 ( Ji et al, 2019 ).…”
Section: Discussionmentioning
confidence: 89%
“…An increasing amount of experimental evidence demonstrated that the proliferation and apoptosis of mammary epithelial cells had influences on the development of the mammary gland, milk secretion, and lactation [ 25 , 26 , 27 ]. Using the siRNA strategy, we found that both AGPAT1 and AGPAT6 knockdown could suppress proliferation and apoptosis of BuMECs.…”
Section: Discussionmentioning
confidence: 99%